Roflumilast – a phosphodiesterase-4 inhibitor licensed for add-on therapy in severe COPD (Swiss Medical Weekly, 2012)
Roflumilast is a selective phosphodiesterase 4 inhibitor which has been licensed in the European Union since 2010 and in Switzerland since November 2011 as an add-on treatment for patients with chronic obstructive pulmonary disease (COPD) in GOLD (Global Initiative for Chronic Obstructive Lung Disease) stages 3 and 4 (FEV1